Keberkesanan Pengurusan Fasiliti Bilik Kuliah Di UTHM Semasa Peralihan Fasa Endemik Covid-19 - Shamsuddin, Muhammad Firdaus; Shareh Musa, Sharifah Meryam; Zainal, Rozlin; Kasim, Narimah (Research in Management of Technology and Business, 2023)
Facilities Management is an organizational system that combines people, places, and processes in the built environment with the goal of improving people's quality of life. The problem statement for this study is related to the effectiveness of the management of lecture room facilities at UTHM during the transition to the endemic phase of Covid-19 where there was an issue of objections to conducting lectures physically and end-of-year examinations were conducted face-to-face. The objective of this study is to identify the steps taken in the management of lecture room facilities from the aspects of planning, maintenance, service provision, SOP compliance and to examine the effectiveness of UTHM in managing lecture room facilities during the transition phase of the endemic phase of Covid-19. Next, the scope of the study was at Universiti Tun Hussein Onn, Parit Raja, Johor. Qualitative methods were conducted to answer the research questions. The researcher interviewed the parties involved in the management of the lecture room facility consisting of Academic Management Office (PPA), Development and Maintenance Office (PPP), Strategic and Risk Management Office (PSPR), and Faculty directly and indirectly involved to achieve the first and second objectives. In relation to that, the findings of the study found that the main problem in the steps taken in the management of lecture room facilities from the aspects of planning, maintenance, service provision, SOP compliance and examining the effectiveness of UTHM in managing lecture room facilities is due to aspects of planning, maintenance, and SOP compliance in the lecture hall/room. In conclusion, this study is also expected to give a clear picture of the steps and effectiveness in the management of lecture room facilities at UTHM as well as provide safety, health, and comfort to all parties involved directly and indirectly.